Synthesis and characterisation of nanohybrid anti-hypertensive drug, captopril intercalated into zinc-aluminium layered double hydroxide [Sintesis dan pencirian nanohibrid ubat anti-hipertensi, captopril tersisip ke dalam zink-aluminium hidroksida berlapis ganda] - Zaemah J.; Sarijo S.H.; Jadam M.L.A. (Malaysian Society of Analytical Sciences, 2023)
Captopril (CPL), an anti-hypertensive drug was intercalated into the interlayer spaces of zinc-aluminium layered double hydroxide (ZLDH) for the formation of zinc-aluminium-captopril (ZCPL) hybrid nanocomposite material by self-assembly method. The concentration of CPL used was 0.08 M with pH 7.5 in a constant 3:1 molar ratio of zinc (Zn) to aluminium (Al) in the mother liquor. As a result of the successful intercalation of CPL, powder X-ray diffraction pattern (PXRD) shows the basal spacing increased from 8.90 in ZLDH to 9.69 in the ZCPL nanohybrid material. Fourier transform infrared (FTIR) spectroscopy study shows the intercalated compound of ZCPL resembled the spectra of ZLDH and CPL, thus indicating the presence of both functional groups in ZCPL spectra. CHNS analysis shows the ZCPL nanohybrid material contains 30.63% (w/w) of CPL which was calculated based on the percentage of carbon in the sample. It was also found that the BET surface area increased from 1.7 m2/g in ZLDH to 10.9 m2/g in ZCPL. The pore texture of the resulting material was also changed as the result of the intercalation and the expansion of the basal spacing during the formation of the layered intercalated ZCPL nanohybrid material. 2019, Malaysian Society of Analytical Sciences. All rights reserved.